2017
DOI: 10.1111/bjh.14684
|View full text |Cite
|
Sign up to set email alerts
|

Targeting anti‐apoptotic BCL2 family proteins in haematological malignancies – from pathogenesis to treatment

Abstract: The B-cell lymphoma 2 (BCL2) family of proteins comprise key regulators of apoptosis and are implicated in the pathogenesis of many malignancies, including lymphomas and leukaemias. Targeting of BCL2 proteins can be directly toxic to tumour cells or render them more sensitive to chemotherapy. Inhibition of the anti-apoptotic functions of BCL2 proteins using structure-based design to produce specific inhibitors of protein-protein interactions has been achieved for BCL2, MCL1 and BCL-X (also termed BCL2L1), prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 94 publications
3
68
0
2
Order By: Relevance
“…Bcl-2 as an anti-apoptotic protein plays an important role in apoptosis regulatory (Vogler et al, 2017). In the present study, we observed the increase of Bcl-2 by the up-regulation of miRlet-7i.…”
Section: Discussionsupporting
confidence: 68%
“…Bcl-2 as an anti-apoptotic protein plays an important role in apoptosis regulatory (Vogler et al, 2017). In the present study, we observed the increase of Bcl-2 by the up-regulation of miRlet-7i.…”
Section: Discussionsupporting
confidence: 68%
“…To prevent the opening of the mitochondrial outer membrane, BCL2L1 binds to Bax and Bak and inhibits their oligomerization, and thus functions as an antiapoptotic factor. 49 We demonstrated the upregulation of BCL2L1 in PCa in comparison with peritumoral tissues. MiR-608 overexpression induced significant apoptosis in PCa by directly targeting BCL2L1 through BCL2L1/ caspase-3 signaling pathway.…”
Section: Discussionmentioning
confidence: 67%
“…Next, caspase‐3 is activated by cytochrome C and initiates serial downstream apoptotic responses. To prevent the opening of the mitochondrial outer membrane, BCL2L1 binds to Bax and Bak and inhibits their oligomerization, and thus functions as an antiapoptotic factor . We demonstrated the upregulation of BCL2L1 in PCa in comparison with peritumoral tissues.…”
Section: Discussionmentioning
confidence: 68%
“…The balance of cell survival and apoptosis signaling pathways is critical for determining the fate of cells, and multiple genes and molecules are involved in the regulation of this balance (25). Bcl-2 family proteins serve key roles in regulating cell apoptosis (26), and the results of the present study indicated that TW37 reduced the expression levels of the anti-apoptotic protein Bcl-2, as well as induced apoptosis of H1975/EGFR-TKI cells.…”
Section: Discussionmentioning
confidence: 56%